The Impact of Social Media Marketing on Gen Z Males' Purchase Intention of Facial Wash Product - Malikahasri, Karindra (Integrasi Sains Media, 2023)
The worldwide cosmetics sector is expanding quickly in the modern period due to rising consumer demand. More and more people, regardless of gender, strive to achieve visual appeal and good health. The worldwide cosmetics sector has seen tremendous growth in the popularity of skincare products. Male skincare product consumers are growing due to changing lifestyles and heightened self-awareness. Earlier research indicates that social media has a significant role in luring males to purchase skincare products. Knowing how effective social media marketing is towards Gen-Z males' purchase intention is essential. Thus, there is a need for a comprehensive examination to be carried out. The primary objective of this research is to determine whether social media marketing has a direct or indirect impact on the purchase intention of facial wash brands. This research is conducted using a quantitative approach, utilizing a survey distributed towards 306 respondents Gen-Z males who live in Bandung aged 18 - 26, have previously purchased facial wash products from any brand, and use social media frequently. The data that was collected was analyzed using descriptive statistics and PLS-SEM. The result of the analysis shows that social media marketing has a direct and positive impact on purchase intention. However, their relationship seems to be on the low-to-average level. In order to strengthen their relationship, it is found that the mediator variables, which are brand image, brand trust, and brand loyalty, are needed. Therefore, to effectively use social media marketing to influence purchase intention, brands have to consider building a good brand image, brand trust, and brand loyalty. The findings of this research can be utilized by marketers who intend to create purchase intention through social media marketing.